An Overview of Information Visualization for Malay Poetry Studies - Noh, Zakiah; Z. Abidin, Siti Z.; Omar, Nasiroh; Aliman, Sharifah; Ardi, Norizah (2018)
Information visualization is an application that represents data in a graphical form and meaningful way.In poetry studies, graphics can offer an excellent approach for exploring and presenting features of poetic elements. The significances of representing the poetic features by using graphics in visualization are to provide users with better understanding of poem features and expose the details of texts elements.In recent years, several significant studies have focused on visualization of poem elements.This paper summarizes the visualization of poetry studies and provides analytical views for the potential of information visualization in the Malay poetry study.Various kind of research in this area may assist other researchers to gain insight into the research trends and benefits towards the literary field for exploring text analytics.